IMPLEMENTASI PROGRAM 7 KEBIASAAN ANAK INDONESIA HEBAT DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SD NEGERI 104251 KARANG ANYAR - Febri Annisa Sella; Apiek Gandamana; Nurmayani; Waliyul Maulana Siregar; Yusra Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of students' disciplinary character is one of the primary goals of elementary education to foster obedience to rules, responsibility, and orderly behavior. However, various forms of undisciplined behavior are still found among students, indicating the need for an effective character habituation program. This study aimed to describe the implementation of the Seven Habits of Great Indonesian Children Program in developing students' disciplinary character and to identify the supporting and inhibiting factors in its implementation at SD Negeri 104251 Karang Anyar. This study employed a qualitative research design with a case study approach. The research informants consisted of the principal, the Grade IV-B classroom teacher, and Grade IV-B students. Data were collected through passive participant observation, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that the Seven Habits of Great Indonesian Children Program was systematically implemented through daily and weekly habituation activities integrated into school routines. The program contributed to the development of students' disciplinary character, particularly in time discipline, religious discipline, learning discipline, and social discipline. Supporting factors included the commitment of the principal and teachers, adequate school facilities, students' active participation, structured habituation programs, and communication with parents. Meanwhile, the inhibiting factors included inconsistent student behavior, limited parental supervision at home, and unequal parental support. Therefore, the program has positively contributed to strengthening students' disciplinary character and should be reinforced through sustainable collaboration between schools and families to maximize its effectiveness.